The effect of hot-stamping process on the local electrochemical behaviour of the 22 MnB5 steel coated with hot-dip aluminium-silicon - Couto, Camila Pucci (2021)
Press-hardened steel (PHS) is a strategic steel for the automotive industry. The application of this type of steel in the vehicle structure allows safety improvement, mass reduction and less fuel consumption. Due to its ultra-high-tensile strength, the PHS components are produced by means of hot-stamping process. Hot stamping is a thermo-mechanical process in which a steel blank is heated at austenitisation temperatures and then is transferred to a press tool, where the material is formed and quenched simultaneously. The steel substrate is often protected with metallic coatings prior to hot stamping to avoid its oxidation and decarburisation. Zinc and aluminium based systems are often used as coatings for automotive applications. However, for hot stamping, the hot-dip aluminium-silicon (Al-Si) system is the most widespread and used. This coating presents good corrosion and oxidation resistance at high temperatures. However, during hot stamping, the initial microstructure and chemical composition of the metallic coating changes completely due to diffusion. These microstructural and compositional changes take place in the austenitisation step. Hence, after hot stamping the whole coating layer becomes a complex multi-layered system in which the sublayers are enriched in either aluminium or iron/silicon. Consequently, the coating properties, including the corrosion properties, also change after hot stamping. However, little is known about the effect of the morphological and compositional changes of the Al-Si coating due to the thermo-mechanical process on its corrosion behaviour and performance. The different sublayers in the coating form different micro-galvanic-couplings, which can affect the global electrochemical behaviour of the system. Therefore, a detailed approach based on local electrochemical techniques was suggested to evaluate the role that each sublayer plays on the electrochemical behaviour. This work aimed at evaluating the effect of the hot-stamping process on the electrochemical behaviour of 22MnB5 coated with hot-dip Al-Si (10 % Si in mass fraction). The morphology-composition of the layered structure was obtained using field emission scanning electron microscopy (FE-SEM) combined with energy dispersive X-ray spectroscopy (EDS). Global corrosion properties were evaluated by open circuit potential (OCP), linear sweep voltammetry (LSV) and accelerated corrosion test. Nonetheless, the effect of each sublayer of the coating-steel system, on the electrochemical behaviour was investigated on a local scale by two complementary techniques: scanning Kelvin probe force microscopy (SKPFM) and electrochemical micro cell. The former was carried out in the samples\' cross-section and it shows high lateral resolution, while the latter was done from the top surface in a depth profile approach. Thus, it enabled the local potentiodynamic polarisation in an isolated sublayer. The results obtained during the implementation of this work highlight the high complexity of the Al-Si coating-steel system (composed of several layers), which in turn supports the need for local investigations. The morphology and composition of the coating were shown to be greatly influenced by the hot-stamping process (parameters) and this resulted in considerable variations of the local corrosion and electrochemical behaviour of the coating-steel system.